Comparative evaluation of pre- and postoperative administration of citicoline: clinical outcomes and the volume of ischemic brain damage after meningioma removal - G. Z. Sufianova; A. G. Shapkin; A. A. Sufianov; M. S. Khlеstkina; R. A. Sufianov; A. M. Mashkin (Сеченовский вестник, 2019)
In the experimental model of cerebral ischemia, citicoline has shown greater eﬀectiveness with its preventive use compared with therapeutic one.Aim. To study the main clinical outcomes and the dynamics of morphometric indicators of ischemic brain damage according to computed tomography (CT) data in patients with meningiomas of the skull base in the postoperative period against the background of prophylactic and therapeutic administration of citicoline.Materials and methods. The study included 53 patients aged 40 to 69 years with the skull base meningiomas. The ﬁrst (control) group (n=17) and the third group, in which citicoline was administered in the postoperative period for 7–21 days at a dose of 1000 mg 2 times a day intravenously (n=25), were formed retrospectively. The second group (n=11), in which citicoline was administered prophylactically 1.5–2.5 hours before surgery at a dose of 2000 mg intravenously, was formed prospectively. We evaluated the main clinical outcomes and CT morphometry data.Results. The average time spent in the intensive care unit was minimal in the second group: 9.6±3.2 days vs 17.6±3.7 days in the control (p=0.049). Postoperative mortality was 24% in the control group, 9% in the second group, and 20% in the third group. The survival time in the ﬁrst group was less than 21 days, over 21 days in the second and third groups. The groups did not diﬀer in neurological outcomes and overall in-hospital stay. The average volume of ischemic brain damage on the ﬁrst day after surgery in the second group was less than in the control group, and amounted to 111.7±15.2 cm3 against 151.3±17.1 cm3, respectively (p=0.044).Conclusion. The prophylactic administration of citicoline before a tumor removal operation may have eﬀective potential for reducing the severity and prevalence of ischemic cerebral edema. Further randomized clinical trials are needed.